Factors determining the effect of financial risk in the entrepreneurial environment of small and medium-sized enterprises in the Czech Republic - Jaroslav Belas; Jan Dvorsky; Jan Kubalek; Lubos Smrcka (Institute of Economic Research (IER), 2017)
Research background: Entrepreneurs enter into business with the aim of gaining the maximum possible profit. They are increasingly willing to tolerate the effect of a greater intensity of financial risk. Factors which influence the intensity of financial risk in a business are related not only to the securing of financial resources, but also to crucial decisions on the parts of entrepreneurs or the ability to manage financial risk during a crisis in small and medium-sized enterprises (SMEs). Aim of the article: The aim of the article is to define and quantify the significance of factors which influence, by their character and effect, the intensity of financial risk in the SME entrepreneurial environment. Methodology/methods: The selection set represented 1,141 SMEs. It was carried out in the Czech Republic in 2015. We used the 'inquiring in the form of an online questionnaire' method of ascertaining data. To fulfil the main aim, we used the methods of regression and correlation analyses with the aim of determining the relationship between the intensity of financial risk and the determinants thereof. In the first step, we carried out descriptive statistics (pivot table, scatter plot, skewness, kurtosis, normal distribution plot, and histogram). In the second step, we verified assumptions by carrying out regression modelling and by testing the normal distribution of data in determinants, the assumption of linearity, multicollinearity and homoscedasticity of variables (t-test, z-test, VIF test, Bartlett's test, F-ratio), and interpreted the results (estimate coefficient of parameters, coefficient correlation, coefficient determination). All the realised tests were carried out on a 0.05 level of significance using IBM SPSS Statistics, Version 23 software. Findings & Value added: On the basis of the results of the questionnaire investigation and using regression and correlative data analysis, we quantified the statistical significance of determinants which influence the intensity of financial risk in the SME segment. The result of key factors serves as a basis for proposing measures in the context of preventing a business from the intensity of financial risk.
Keywords: L26; 330; financial risk; doing business; entrepreneur; management